Kebijakan Hukum Pidana terhadap Kejahatan Cyber Studi Perbandingan Antara Indonesia dan Thailand dalam Perspektif Hukum Internasional - Aulia Mawaddah Matondang (CV Rewang Rencang, 2025)
This study discusses a comparison of criminal law regulations against cybercrime in Thailand and Indonesia, as well as the challenges faced in their enforcement. This normative research uses a legislative approach to evaluate the effectiveness of the legal frameworks of both countries in preventing and dealing with cybercrime. Thailand relies on the Computer Crime Act (CCA) which focuses on various types of cybercrime, while Indonesia has the Information and Electronic Transactions Law (ITE Law) which regulates more broadly aspects of digital transactions and information dissemination. The study found that although the legal framework in both countries is quite comprehensive, limited human resources and technical skills are major challenges in law enforcement against cybercrime. Cyber law enforcement requires very high technical skills, and many law enforcement agencies in both countries still lack personnel who have competence in information technology and cybersecurity. Another important aspect of this study is international cooperation which is key in tackling cross-border cybercrime. Thailand and Indonesia, like other countries, deal with cybercrime that often involves perpetrators and victims in various countries. In this regard, international conventions such as the Budapest Convention on Cybercrime play an important role. The Convention provides an international legal basis for cooperation in combating cybercrime, including procedures for requesting legal assistance and extradition. In addition, international organizations such as Interpol also play an important role in the coordination and exchange of information between countries to deal with cybercrime. The results of this study show that further efforts are needed in terms of inter-agency coordination, law enforcement training, and public education to improve protection against cybercrime in Thailand and Indonesia. Closer international collaboration, both through bilateral and multilateral forums, is also very important to increase the effectiveness of cyber law enforcement.